Histopathological examination of healing in bone defects in intermittent fasting: An experimental study - Can, Koray; Tanrisever, Murat; Ozcan, Erhan Cahit; Dogan, Delil; Istek, Ozmen; Donmezer, Tugce; Dundar, Serkan (Univ Zulia, Facultad Ciencias Veterinarias, 2026)
The aim of this study is to histopathologically examine the effect of intermittent fasting, which has been followed with interest by researchers recently, on the healing of bone defects created in rat tibias. Sixteen Sprague-Dawley rats were included in this experimental study. For this purpose, the rats were divided into two groups: a defect control group (n = 8) and a defect + fasting group (n = 8). In the defect groups, a 4 mm diameter and depth defect was created in the corticocancellous bone of the metaphyseal tibia. Intermittent fasting was applied to the fasting groups three days a week for eight weeks. All animals were sacrificed at the end of the process, and the tibias were decalcified and examined histopathologically, with new bone formation and callus were assessed. Data were analyzed statistically. Student's t-test was used for statistical analysis. The mean longitudinal defect size value for the control group was 1675.43, while that of the fasting group was 1594.29. The mean vertical defect size value for the control group was 576.86, while that of the fasting group was 528. And the mean callus size value for the control group was 145, while that of the fasting group was 154.14. Both bone formation and callus values were numerically higher in the fasting group compared to the control group. However, these differences were not statistically significant (P>0.05). Based on the limited results of this study, although intermittent fasting may have a potential biological effect in supporting bone healing, no statistically significant difference was found in this study.
Keywords: Intermittent Fasting; Bone Defect; Bone Healing; Bone Regeneration; Rat Tibia